Affective engagement in academic reading: What EFL student teachers reveal - Made Frida Yulia; Gunadi Harry Sulistyo; Bambang Yudi Cahyono (Institute of Advanced Engineering and Science, 2020)
Academic reading is an inescapable task in higher education. Due to its importance for study success, students are required to maintain their academic reading engagement. With engagement, they would be enabled to persevere and be more spirited in their reading efforts. However, not all students perceive academic reading positively, particularly in EFL learning environment where English reading is seen as something daunting. Academic reading engagement is essentially determined by a number of dimensions, one of which is affective dimension. This research aims to portray the affective dimension of the academic reading engagement among student teachers of English as a Foreign Language (EFL) in a teacher-training university in Indonesia. Eight EFL student teachers were selected from three classes of an English content course which required a lot of academic reading. These student teachers were interviewed using a semi-structured guide. The results show that many EFL student teachers’ efforts in coping with course-related reading materials were externally driven. They showed low liking for learning, demonstrated little enthusiasm, interest, enjoyment, and confidence in relation to academic reading. Also, they did not always understand the values of academic reading and text relevance for their development as teachers.